1977
DOI: 10.1073/pnas.74.3.1272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early experience upon orientation sensitivity and binocularity of neurons in visual cortex of cats.

Abstract: The class of neurons within the visual cortex of normal adult cats that has the smallest receptive fields (<2.25 degrees2) and that responds only to low rates of stimulus motion (S5O0/sec) responds preferentially to lines oriented about either the horizontal axis (+22.50) or the vertical axis (±22.50). In animals reared without exposure to patterned visual stimulation, many of these cells display orientation preferences but are activated monocularly. In contrast, in normal animals, neurons that have larger rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…In vision, for example, a central mechanism is thought to be responsible for anisotropy (De Valois, Yund, & Hepler, 1982;Leventhal & Hirsch, 1977;Mansfield, 1974;Mansfield & Ronner, 1978;Orban & Kennedy, 1981). In visual anisotropy, greater sensitivity is found for vertical and horizontal orientations than for the oblique orientation.…”
Section: Spatial Measures Of Anisotropymentioning
confidence: 99%
“…In vision, for example, a central mechanism is thought to be responsible for anisotropy (De Valois, Yund, & Hepler, 1982;Leventhal & Hirsch, 1977;Mansfield, 1974;Mansfield & Ronner, 1978;Orban & Kennedy, 1981). In visual anisotropy, greater sensitivity is found for vertical and horizontal orientations than for the oblique orientation.…”
Section: Spatial Measures Of Anisotropymentioning
confidence: 99%
“…Investigators reported that in both developing and adult ferrets, larger areas were activated by horizontal and vertical contours than by oblique contours (Chapman and Bonhoeffer 1998;Chapman et al 1996;Coppola et al 1998;Rao et al 1997;White et al 2001). In cats and kittens, some electrophysiological (Albus 1975;Bauer and Jordan 1993;De Valois et al 1982;Fregnac and Imbert 1978;Kennedy and Orban 1979;Leventhal and Hirsch 1977;Mansfield and Ronner 1978;Payne and Berman 1983;Pettigrew et al 1968) and optical imaging (Dragoi et al 2001;Muller et al 2000) studies have suggested that more cortical cells tend to display horizontal or vertical preferences, and cortical cells preferring horizontal or vertical orientations are more narrowly tuned (Kennedy and Orban 1979;Rose and Blakemore 1974) in the primary visual cortex. However, investigators have largely ignored the fundamental question of how much the representation of a given angle overlaps with the representation of nearby angles.…”
Section: Introductionmentioning
confidence: 99%
“…There is some reason to believe that the precise nature of these cortical deficits depends on whether binocular deprivation results from lid suture as opposed to dark-rearing . Of intriguing significance are the findings of Blakemore and Van Sluyters (1975) and of Leventhal and Hirsch (1977): In binocularly deprived cats, those cortical cells which are orientation selective tend to be of the simple type. This raises the possibility that the normal array of X cells in the LON of binocularly deprived cats is projecting to simple cells in layer IV of visual cortex, thereby providing some substrate for orientation selectivity.…”
Section: Monocular and Binocular Deprivationmentioning
confidence: 97%